New thiamine functionalized silica microparticles as a sorbent for the removal of lead, mercury and cadmium ions from aqueous media - (:unkn) unknown (SERBIAN CHEMICAL SOC, 2017)
The existence of heavy metal ions in aqueous media is one of the biggest environmental pollution problems and thus the removal of heavy metals is a very important procedure. In this work, a new adsorbent was synthesized by modifying 3-aminopropyl-functionalized silica gel with thiamine (vitamin B1) and characterized. The influence of the uptake conditions, such as pH, contact time, initial feed concentration and foreign metal ions, on the binding capacity of thiamine-functionalized silica gel sorbent (M3APS) were investigated. Maximum obtained adsorption capacities for Pb(II), Hg(II) and Cd(II) were 39.4+/-0.2, 30.9+/-0.5 and 9.54+/-0.4 mg g(-1) M3APS, respectively, at pH 5.0. The observed selectivity of M3APS for these metal ions was the following: Pb(II) > Hg(II) > Cd(II). Adsorption isotherm models were also applied to the adsorption process. As a result, the Langmuir isotherm model gave the best fit for the adsorption of metal ions on M3APS. The Gibbs energy change (Delta G) for the adsorption of Pb(II), Hg(II) and Cd(II) were calculated to predict the nature of adsorption process. Having such satisfactory adsorption results, M3APS is a potential candidate adsorbent for Pb(II) and Hg(II) removal from aqueous media.
Keywords: heavy metal ions; adsorption; AAS; environmental remediation; HEAVY-METALS; SOIL-PH; ADSORPTION; HYDROGELS; EXTRACTION; RECOVERY; SULFUR; ZINC; PB2+